Kesiapan Kerja Siswa SMK Muhamadiyah 2 Paleran dalam Memasuki Dunia Kerja Ditinjau dari Kompetensi dan Motivasi Diri - Redjeki, Sri (Education Journal : Journal Educational Research and Development, 2024)
Vocational High Schools are intended for students who want to work immediately after graduating. Ideally, Vocational High Schools are able to produce graduates who are ready to work. However, statistical data shows that Vocational High School graduates are the highest contributor to the unemployment rate at the level of High School graduates. This research aims to determine the work readiness of students at SMK Muhamadiyah 2 Paleran in entering the world of work. The research subjects were class XII students majoring in Online Business and Marketing. The research uses a qualitative research approach with simple descriptive statistical analysis. Students' work readiness is viewed from a competency perspective consisting of: knowledge, English language skills, and skills in using computers and the internet. Student work readiness is viewed from the perspective of self-motivation, referring to self-motivation and support from the school. The research results showed that in terms of competency, 15% of students said they were very ready to enter the world of work, 72% of students were quite ready, 13% of students said they were still not ready. However, they have weaknesses in English language skills. In terms of motivation, 83% of students said they were very ready to enter the world of work, 12% of students were quite ready. Support from the school also greatly contributes to student motivation. Based on the data above, it can be concluded that students at SMK Muhamadiyah 2 Paleran are ready to enter the world of work after graduating from vocational school.